(untitled) (Docentes 2.0 Journal, 2024)
The emergence of COVID-19 was a phenomenon that substantially affected the population. Due to the ease of contagion, health organizations such as the World Health Organization (WHO) implemented measures to contain the virus that causes multiple symptoms. The objective was to analyze the impact of the COVID-19 pandemic on physical activity and health, given previously carried out studies. The research was based on a positivist paradigm, using meta-analysis by PRISMA statement, with a qualitative approach, non-experimental design, descriptive type, and cross-section, where the systematic review of 21 articles extracted from Redib, SD, Esci, Cumed, PubMed, Scopus, Scielo, Dialnet, Redalyc Latindex, Google Scholar and others hosted by the International University of Andalusia and the Revista Odontología Actual. It was determined that 28.5% of articles prioritized people who contracted the virus or were left with consequences of the disease, people in social isolation whose health was in some way harmed physically, psychologically, and socially, 14.2% prioritized ages between 18 and 85 years. Without distinction of sex, only 4.7% of studies prioritized guardians of children from 5 to 7 years old, 4.7% prioritized adult women, 4.7% prioritized middle school and high school students, and 42.8% did not report, concluding that various studies refer to the practice of physical activity as a beneficial and indispensable tool in health as prevention, treatment or rehabilitation in people against non-communicable diseases, consequences of COVID-19, psychological diseases among others.